Evaluation of Crossing Transportation Services on Ships Operating at the Likupang Crossing Port, North Sulawesi Province - Broto Priyono; Monica Amanda; Ranti Halfani (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2022)
Likupang Crossing Port is located in Munte Village, North Minahasa Regency, North Sulawesi. Likupang Port has three ships operating, namely KMP. Lohoraung track Likupang-BiaroTagulandang- Makalehi-Siau, KMP. Tarusi trajectories Likupang-Pananaru-Melonguane and KMP. Watunapato trajectory Likupang-Melonguane-Marampit-Miangas which is currently docking. Based on the results of observations in the field, there are some services that have not been carried out properly, so service users feel dissatisfied and uncomfortable while on the ship. The method for analyzing existing problems is the analysis of the percentage of the level of conformity of crossing transportation service standards and the analysis of Importance Performance Analysis. KMP. Lohoraung with a percentage of conformity rate of 48.58% and KMP. Tarusi with a percentage of conformity rate of 51.61%. On kmp vehicle loading service standards. Lohoraung with a percentage of conformity rate of 85.18% and KMP. Tarusi with a percentage of conformity rate of 81.48%. On the standards of service of operating KMP ships. Lohoraung and KMP. Tarusi has a degree of conformity with a percentage of 100%. Based on the results of the analysis, conclusions were obtained, namely the attributes that are in quadrant I, based on the results of research on important service attributes and received the highest assessment of their importance. Attributes that are in quadrant I include, in KMP. Lohoraung facilities for damaged lifeboats, medical rooms that are not used as they function, unavailability of medical devices (stretchers, wheelchairs, oxygen cylinders), toilets that still merge each gender, no prayer rooms and at KMP. There are leaky lifeboats, toilets still joined by each gender, nursing rooms that are not used as they function, lighting that does not comply with the rules.